A perspective on the Motivation to Comply social norms construct - Paul Branscum (New Prairie Press, 2022)
This social norms construct, motivation to comply (MTC), has been labeled problematic. To understand how MTC has been operationalized and measured, a scoping review was conducted. To retrieve articles, the key words 'Motivation to Comply' were used in multiple databases (e.g., MEDLINE), from 2009-2021. Twenty-seven manuscripts were identified, and yet according to the author of this study, only 52% measured MTC correctly. Other studies measured MTC as some other psychosocial construct such as attitudes. This article points to the need for standardization in the definition and measurement of the MTC construct.